Guarantee of Information and Communication Technology Application Security in Indonesia: Regulations and Challenges? - Nurfaika Ishak (Audito Comparative Law Journal (ACLJ), 2023)
In this era of rapid development of science, knowledge, and technology, society faces a challenge related to the use of information and communication technology that can be misused by irresponsible parties and can cause harm and loss to others in the form of threats to security stability in cyberspace. This study aims to find out how to guarantee the security protection of information and communication technology applications for Indonesian citizens from the perspective of laws and regulations perspective, then how challenges and opportunities can be addressed to overcome the gaps that occur. This research is normative research with a statutory approach. The data collection technique used in this study is a literature study technique collected by reviewing scientific works, journals, laws and regulations, and other related materials related to information and communication technology, and crimes in cyberspace. The results show that the Indonesian government has issued a law on information and electronic transactions. Furthermore, several work teams were also formed under state agencies/institutions that focused on responding to information security issues such as teams under the auspices of the Ministry of Communication and Information; there were also other teams from Indonesian National Police Agency. The challenges faced are related to law enforcement on the regulations that have been set, namely how the substance of the contents in these regulations can accommodate the protection/guarantee of the security of personal information in Indonesia. In addition, this is also influenced by the apparatus's actions and the community's response.